CONTEXTUAL APPROACH IN TEACHING ENGLISH - Ataxojayev Toxirjon Maxmudjonovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article deals with the use of contextual approach in teaching foreign languages. At resent much attention is aid to the language learning in a contextual environment. The article gives theoretical and practical application of contextual approach in teaching FL